Laparoscopic heminephrectomy in nonfunctioning right moiety of a horseshoe kidney: Technical challenges and method to deal with - Agrawal, Santosh Kumar (Medknow Publications & Media Pvt Ltd, 2014)
Laparoscopic heminephrectomy in patients with horseshoe kidney is technically challenging procedure and only few cases have been reported in the literature. Various approaches have been described for handling the isthmus. We report the management of a case of symptomatic nonfunctioning right moiety of a horseshoe kidney secondary to ureteropelvic junction (UPJ) obstruction using Ligasure™ for vessel sealing and division of isthmus. We discuss here the various challenges during laparoscopic heminephrectomy and ways and tricks to deal with.